2010
DOI: 10.1016/j.mito.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial copy number and risk of breast cancer: A pilot study

Abstract: It has been proposed that the copy number of mitochondria DNA (mtDNA) per cell reflects gene–environment interactions between unknown hereditary factors and exposures affecting levels of oxidative stress. However, whether copy number of mtDNA could be a risk predictor of oxidative stress-related human cancers, such as breast cancer, remains to be determined. To explore the role of mtDNA copy number in breast cancer etiology, we analyzed mtDNA copy number in whole blood from 103 patients with breast cancer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 39 publications
(48 reference statements)
11
103
3
Order By: Relevance
“…The evidence regarding the association between mtDNA copy numbers in peripheral blood cells (PBC) and risk of breast cancer is also limited. In a retrospective study with postdiagnostic blood samples including 103 case-control pairs, Shen and colleagues (8) found that high mtDNA copy number in PBCs was associated with increased risk of breast cancer, and several endogenous oxidants and antioxidants. A small prospective study of 183 breast cancer cases and 529 controls in China also found a similar association with breast cancer risk; however, data suggested that the association was present only in samples collected close to diagnosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence regarding the association between mtDNA copy numbers in peripheral blood cells (PBC) and risk of breast cancer is also limited. In a retrospective study with postdiagnostic blood samples including 103 case-control pairs, Shen and colleagues (8) found that high mtDNA copy number in PBCs was associated with increased risk of breast cancer, and several endogenous oxidants and antioxidants. A small prospective study of 183 breast cancer cases and 529 controls in China also found a similar association with breast cancer risk; however, data suggested that the association was present only in samples collected close to diagnosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, two epidemiological studies that investigated whole blood and buffy coat specimens demonstrated a positive association between mtDNA levels and breast cancer risk (Shen et al, 2010;Thyagarajan et al, 2013). Associations between mtDNA alterations and clinicopathological features of breast cancer have also been inconsistent across studies (Yu et al, 2007;Fan et al, 2009;Xia et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…The leukocyte mtDNA copy number has been investigated in several types of cancer (7,23,24). Several studies observed that a higher cancer risk is likely accompanied by an increase in the mtDNA copy number (21).…”
Section: Discussionmentioning
confidence: 99%